1970
DOI: 10.1002/aja.1001280109
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of shortening and Z line degradation in post‐mortem bovine, porcine, and rabbit muscle

Abstract: Ultrastructural changcs in bovine, porcine, and rabbit muscle have been studied during the first 24 hours post-mortem. Samples were taken for phase and electron microscopy immediately after death, after 4, 8, and 24 hours of post-mortem storage at 2' and 37"C, and after 24 hours post-mortem at 16" and 25°C. The results show that two kinds of structural changes occur in muscle during the first 24 hours post-mortem: ( a ) a variable amount of shortening, this shortening occurring via a sliding of filaments in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

1974
1974
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(30 citation statements)
references
References 14 publications
4
26
0
Order By: Relevance
“…Henderson et al (1970) found that the values for temperature and pH at which shortening occurs depends on the species of animal and muscle type. For beef, shortening was maximal at 2 C, minimal in the range 16À25 C and high again at 37 C in beef (Henderson et al 1970).…”
Section: Meat Quality Effects Of High Temperature and Low Phmentioning
confidence: 99%
See 1 more Smart Citation
“…Henderson et al (1970) found that the values for temperature and pH at which shortening occurs depends on the species of animal and muscle type. For beef, shortening was maximal at 2 C, minimal in the range 16À25 C and high again at 37 C in beef (Henderson et al 1970).…”
Section: Meat Quality Effects Of High Temperature and Low Phmentioning
confidence: 99%
“…Henderson et al (1970) found that the values for temperature and pH at which shortening occurs depends on the species of animal and muscle type. For beef, shortening was maximal at 2 C, minimal in the range 16À25 C and high again at 37 C in beef (Henderson et al 1970). Similarly Honikel et al (1986) found that sarcomeres in excised unrestrained bovine M. sternomandibularis incubated in a water bath shortened by 70% below 6 C, by less than 10% between 6 and 18 C and by 40% between 20 and 38 C. Hwang et al (2004) found however that sarcomere length was no different (P > 0.05) for excised M. longissimus (LL) incubated at 36 C (1.45 mm) than when incubated at 5 C (1.52 mm), with the least at 15 C (1.76 mm).…”
Section: Meat Quality Effects Of High Temperature and Low Phmentioning
confidence: 99%
“…The contractile state of muscle has been reported to be influenced by the ambient temperature, the amount of tension on the muscle, and the postmortem glycolytic rate (Herring et al 1965;Herring 1968 , but that the greatest amount of shortening in excised muscle occurred at lower temperatures (Locker and Hagyard 1963;Henderson et al 1970). In addition, it has been observed that lamb longissimus dorsi muscle was tougher after being exposed to low temperatures during the first 16 h postmortem (Marsh et al 1968 (Jeremiah and Martin 1916, 1917, 1978.…”
mentioning
confidence: 99%
“…Stromer et al (1967) and Henderson et al (1970) observed a progressive slow loss of Z line and M line structures in postmortem muscles. The disappearance or weakening of M line structure was slower than changes in the Z line structure.…”
Section: Some Postmortem Changes In Musclementioning
confidence: 99%
“…The loss of Z-line integrity has been proposed as one cause for the increase in tenderness that occurs in postmortem muscle (Stromer et al, 1967;Davey and Gilbert, 1969;Henderson et al, 1970;and Penny, 1970). The loss of Z line integrity may result in many breaks along the myofibril.…”
Section: B Examination Of the Effect Of Purified Cap On Myofibrilsmentioning
confidence: 99%